Karakteristik Buah Dan Biji Kakao (Theobroma cacao L.) Pada Berbagai Altitude Di Dataran Tinggi - sitohang, nurdin (AGROSUSTAIN, 2025)
The quality of farmers' cacao beans is generally still low today. One of the causes is because they are planted at various altitudes, especially in the highlands. The research focuses on the characteristics of cacao pod and beans at several altitudes in the highlands of North Sumatra. This research is conducted from July 2022 to December 2023 in Simalungun, Karo, Dairi, Samosir, North Tapanuli, and Humbang Hasundutan Regencies of North Sumatra Province. The parameters observed are pod length, pod diameter, pod volume, pod dry weight, bean dry weight, number of beans per pod, average weight per bean at 24 different altitudes between 815 m to 1300 m above sea level, with 10 pieces (replications) respectively in each level. The research results show that the characteristics of cacao pod and beans decrease along with increasing altitude in the highlands. The characteristics of cacao pod and beans in the highlands are still in the normal category compared to those in the lowlands